Analysis of the Impact of Revisions to the Consumer Protection Law in the Digital Era - Erniyanti, Erniyanti (Enigma Institute, 2024)
The development of digital technology has brought significant changes in various aspects of life, including trade transaction patterns. The digital era opens up new opportunities for businesses and consumers, but on the other hand, it also presents new challenges in terms of consumer protection. This research aims to analyze the impact of the revision of the consumer protection law in the digital era. This research uses a qualitative method with a case study approach. Data was collected through interviews with legal experts, businesses, and consumers, as well as analysis of related documents. The research results show that the revision of the consumer protection law has had both positive and negative impacts. The positive impact is that the revision of this law strengthens consumer rights and provides legal certainty in digital transactions. The negative impact is that the revision of this law still has several weaknesses in its implementation.